Acupuncture for management of lower urinary tract symptoms in Parkinson's disease: A protocol for the systematic review of randomized controlled trials. Issue 6 (February 2018) - Kim, Jong-In; Choi, Tae-Young; Jun, Ji Hee; Kang, Hee; Lee, Myeong Soo
Abstract: Background: Acupuncture is claimed to improve the lower urinary tract symptoms (LUTS). Currently, no systematic reviews are performed for acupuncture on LUTS in patients with Parkinson's diseases (PD). This review aims to evaluate the current evidence on the efficacy of acupuncture for the management of LUTS in PD. Methods and analyses: Eleven databases will be searched from their inception. These include PubMed, AMED, EMBASE, the Cochrane Library, 6 Korean medical databases, and 1 Chinese medical database. Study selection, data extraction, and assessment will be performed independently by 2 researchers. Risk of bias will be assessed with the Cochrane risk of bias assessment tool. Ethics and dissemination: Ethical approval will not be required, given that this protocol is for a systematic review. The systematic review will be published in a peer-reviewed journal and disseminated both electronically and in print. The review will be updated to inform and guide healthcare practice and policy. Trial registration number: PROSPERO 2018 CRD42018083857